2020
DOI: 10.1371/journal.pone.0229008
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and feasibility of a combined rapid assessment of avoidable blindness and hearing loss protocol

Abstract: This study has two main objectives: 1) to assess the value of combining the rapid assessment of avoidable blindness (RAAB) and the recently developed rapid assessment of hearing loss (RAHL) based on existing population-based data from Cameroon andIndia; 2) to test the feasibility of a combined RAAB-RAHL protocol. Methods A secondary data analysis of population-based disability surveys in India and Cameroon (in 2013-2014) was conducted, focussing on people aged 50+. Hearing impairment (HI) was defined as pure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 22 publications
(29 reference statements)
0
16
0
Order By: Relevance
“…Automated test protocols and intuitive user interfaces on these smartphone screening apps allow lay health workers (LHWs) or community health workers (CHWs) to facilitate hearing and vision testing (Bright et al, 2020;Eksteen et al, 2019;Jayawardena et al, 2020;Rono et al, 2018;Yousuf Hussein et al, 2016;. A recent study confirmed that training CHWs in primary ear and hearing care identification can be feasible and accurate (Bright et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Automated test protocols and intuitive user interfaces on these smartphone screening apps allow lay health workers (LHWs) or community health workers (CHWs) to facilitate hearing and vision testing (Bright et al, 2020;Eksteen et al, 2019;Jayawardena et al, 2020;Rono et al, 2018;Yousuf Hussein et al, 2016;. A recent study confirmed that training CHWs in primary ear and hearing care identification can be feasible and accurate (Bright et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This combination of VI and HI in an individual is called dual sensory impairment (DSI) 13 . A rapid assessment study of VI and HI conducted among 50 years or older population reported a DSI prevalence of 4.7% 14 . A community-based study from India identified that over one-third of the elderly had DSI 15 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, combined screening can be cost- and time efficient compared to conducting separate screenings. Only three studies indicated the time efficiency of a combined approach ( 11 , 19 , 20 ). For preschool and school-aged children, combined screening can be completed within ~3–8 mins ( 11 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…A combined service can extend the value of available resources as the population groups most affected by hearing problems are often the same as those with the highest burden of vision problems, i.e., older adults and children of school-going age. Furthermore, using the same screening personnel may reduce time, and associated costs as screeners can receive combined training and share resources ( 19 ). Recent studies have demonstrated that identification and diagnosis of hearing and vision impairments is possible in community-based programs ( 11 , 20 ).…”
Section: Introductionmentioning
confidence: 99%